TYPES OF TRANSLATION USED IN THE FIELD OF LITERARY WORKS - Inog’omjonova Robiya Rustamjon qizi (Western European Studies, 2024)
This article provides a comprehensive description of translation types which are widely used in literary works. It elaborates on the classification of translation types, the functions of translation methods used in the translation process, and detailed explanations about translation norms and transformation as well. The distinct characteristics of these types are extensively highlighted. L.S.Barhudarov and Y.N.Komissarov's classification types are thoroughly explained. Additionally, some issues related to these types are analyzed, and the most specific features unique to each identified translation type are outlined
Keywords: Translation; literary text; types of translation